Currency devaluation and international competitiveness : the case of the CFA zone of West and Central Africa / Dosse Toulaboe - Toulaboe, Dosse (Faculty of Business and Management ; UiTM Press, 2002)
The lack of external competitiveness in the CFA zone resulting from an appreciation of the CFA franc and deterioration of the terms of trade, is believed to be one of the major causes of the poor performance of the zone in the 1980s and early 1990s. The objective of this study is to investigate the effects of a nominal CFA devaluation on the external competitiveness of the CFA zone. Based on pooled cross-section timeseries data regressions, the real effective exchange rate (a measure of external competitiveness) is found to be strongly related to productivity, terms of trade, trade policies and, most importantly, nominal CFA devaluation. The results indicate that a nominal devaluation of the CFA franc can help the zone regain (or maintain) its international competitiveness.